Long-term over-the-horizon microwave channel measurements and statistical analysis in evaporation ducts over the Yellow Sea - Wang, Shuwen; Yang, Kunde; Shi, Yang; Zhang, Hao; Yang, Fan; Hu, Dawei; Dong, Guoyu; Shu, Yihang (Frontiers in Marine Science, 2023)
Maritime high-speed over-the-horizon wireless communication is realizable through evaporation ducts. Detailed measurement, analysis, and modeling of duct channels are essential for application of this communication technique. In this paper, X-band electromagnetic (EM) wave propagation systems were developed and deployed for a 133-km over-the-horizon microwave link in coastal areas of the Yellow Sea. The propagation length was 7.7 times the line-of-sight length. Measurement results including the path loss (PL) and meteorological data were obtained during a 54-day period in autumn 2021. The long-term channel results were analyzed on the basis of statistical analysis and model simulations. Results showed that our measurement system, with a maximum measurable power loss of 200 dB, had connected with a probability of 56.2% during the measurement period. Model simulation showed that evaporation duct environments are not ideal in autumn, with an average evaporation duct height (EDH) of 10.6 m. The land breeze in autumn introduced dry and cold air to the link, which could promote evaporation of seawater and reduce PL by approximately 40 dB. Annual spatiotemporal characteristics of EDH showed that evaporation ducts are most suitable for over-the-horizon communication in spring, especially May.